The biomechanics of atherosclerosis development - Makinde, Oluwole D.; Acho, Thomas M.; Sibanda, Precious; Lungu, Edward M. (Computer Assisted Methods in Engineering and Science, 2003)
In this paper, we investigate the bio-mechanics of atherosclerosis development in human physiology. Blood is modelled as an incompressible fluid of variable viscosity flowing in a slightly diverging channel (i.e. large artery) of small aspect ratio [15]. The hypothetical viewpoint in this work is the existence of relationship between the atherosclerosis development, blood viscosity, flow separation and turning points in the flow field. The problem is tackled by asymptotic approximation and the graphical results are discussed quantitatively.